The Integration of Islam and Local Culture in Okol Tradition in Madura: Integrasi Islam dan Budaya Lokal dalam Tradisi Okol di Madura - Firdausi, Jamilatul; Muhsin, Imam (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2024)
The presence of Islam in the Nusantara contributes to the diversity of cultures in the Nusantara, which then forms Islamic traditions in various regions. One of them is the Okol tradition in Madura, East Java. This study aims to examine the integration of Islamic values and local culture in the Okol tradition, especially in Madura. There are three discussions, namely the explanation of the relationship between Islam and local culture, the history and development of the Okol tradition in general and specifically in Madura, and the last is analysis of the integration of Islamic values and local culture in the Okol tradition. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation to get accurate and in-depth results. Researchers also relied on articles and news to support the research. This research produces several important points, namely that religion and culture have a close relationship. Islam without culture has no form. Then, the Okol tradition is a tradition carried out from generation to generation by the Madurese community to wait for the rain to come. The analysis of the Okol tradition confirmed that the mixing of Islamic values with local culture is real, which can be observed from the Okol events series such as the Okol orchestra, the reading of Du'a, and the wrestling match. This study is expected to provide a clearer description of Islamic values and local culture in the Okol tradition in Madura.